Pulsed ultra-violet laser interactions with ultra-low-density porous carbon nanotube sponges. (November 2015) - Chen, Jikun; Gui, Xuchun; Lin, Zhiqiang; Tang, Zikang; Lee, Michael M.; Wokaun, Alexander; Lippert, Thomas
Abstract: In order to improve the understanding of laser interactions of materials with homogeneous nano-structures, pulsed laser induced plasma from a low density, high-porosity multiwall carbon nanotube (CNT) sponge and a dense graphite block have been investigated by combinational spectroscopy approaches. We observe distinct differences in the laser-induced light emission of the CNT sponge and graphite block which we attribute to the occurrence of a phase explosion caused by the lower thermal conductivity and weaker mechanical strength of the CNT sponge. Furthermore, spectroscopy plasma analysis reveals that differences in the surface of the two systems play a key role in the generation of negative carbon ions. We observe a more effective production of negative ions for the CNT sponge as compared to the graphite block due to the greater number of surface defects of the CNT sponge.